Kritik dan Refleksi terhadap Pemikiran Hadits Kontemporer: Sebuah Pendekatan Interdisipliner dalam Konteks Sosial, Politik, dan Budaya - Ahmad Haikal; Endad Musaddad (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Contemporary hadith thought emerged as an attempt to address the challenges of modernity, which demands a more contextual understanding of Islamic teachings. Various new approaches, such as historical-critical, hermeneutics, and the maqasid al-shari'ah (the principles of Islamic jurisprudence), have been developed to connect hadith texts with modern social, political, and scientific realities. This article examines critiques and reflections on contemporary hadith thought through an interdisciplinary approach. The results show that although contemporary approaches make significant contributions to revitalizing the relevance of hadith, they have weaknesses such as potential relativism, deconstruction of hadith authority, and a disconnect with the classical tradition of hadith scholars. Interdisciplinary reflection offers a middle ground by integrating hadith studies with the social sciences, humanities, and sciences, allowing understanding of hadith to continue to develop without losing its normative authority. This article emphasizes the importance of dialogue between classical traditions and modern approaches in maintaining a balance between fidelity to the text and contextual needs. An interdisciplinary approach to hadith studies can bridge these gaps by fostering dialogue between traditional Islamic scholarship and modern academic fields such as social sciences, humanities, and natural sciences. By combining these disciplines, scholars can explore how hadith texts can be interpreted in ways that are both faithful to their original meaning and responsive to contemporary challenges. This integration can help preserve the normative authority of hadith while addressing modern issues such as ethics, politics, and technology. Ultimately, the interdisciplinary approach provides a framework for reconciling the classical and modern understandings of hadith, ensuring that the teachings of Islam remain relevant and authoritative in today’s rapidly changing world.